The language learned: experience in autism spectrum disorder (Educational Knowledge, 2022)
The experience was developed in the city of Asunción, Paraguay, and its purpose was to find a form of communication between children with Autism Spectrum Disorder and their teachers, in order to achieve their inclusion in the educational and social system. An observation and a record of the codes used by 18 children with Autism Spectrum Disorder to communicate was carried out. At the same time, strategies are also presented that allow teachers to receive them in their classrooms.
Keywords: Language; learned modes; autism spectrum disorder; inclusion; strategies